Innovative composite membranes for advanced applications - Grasso, Giuseppe; Critelli, Salvatore; Gabriele, Bartolo (My University, 2019)
Presented thesis work is mainly focused on coatings preparation, their potentiality and applications in membrane science: from water desalination to antibiofouling membranes, to gas separation. In fact, coating preparation represents an useful and versatile technique which allows a fine control of membrane properties and performance such as chemical or physical resistance, durability, etc. One of major drawbacks is represented by production costs, which can become important in scale-up operations. Therefore, although several type and methodologies for coating preparation are known and reported in literature, a lack of cheap, efficient and scale-up adaptable coating methods made their different preparation methods of particular interest. The results presented herein, concern the preparation of three different coating methods whose applications are briefly summarized below:  Chapter 2: Development of PVDF-f-Graphene Thin Film Composite Membrane for Membrane Distillation Chapter 2 reports a novel method for TFC membrane fabrication, using graphene layer coated on chemically-functionalized PVDF. PVDF is hydrophobic polymer whose properties are well suited for those applications in which hydrophobicity is needed such as Membrane Distillation. In order to increase adhesion between PVDF and graphene, we co-polymerized PVDF with a suitable monomer bearing aromatic part, using a procedure which involves 2 steps reaction: introduction of double bonds on polymer backbone by basic treatment followed by its reaction with monomer through radical reaction. Membranes have been prepared using functionalized PVDF polymer (PVDF-f) and tested on Direct Contact Membrane Distillation (DCMD) apparatus at first. Subsequently tests were conducted using PVDF-f-Graphene composite membrane, using graphene synthetized using Chemical Vapor Deposition ( CVD) method. Created membranes were analyzed and their chemical, physical and morphological properties were investigated. Membranes made using PVDF-f polymer exhibited good flux and salt rejection (up to 99.9 %), whereas graphene association to PVDF-f membranes leads to lower water flux but higher rejection and durability (up to 99.99 %). In chapter 3 a simple and innovative synthetic strategy for Acryloyloxyalkiltriethyl ammonium salts surfactants (AATEABs) starting from cheap and easily available chemicals is discussed. Herein reported surfactants can be used as coating for membranes to whom they confer high anti biofouling properties. Synthetic procedure was first optimized in order to work avoiding prohibitive conditions such as Inert atmosphere or high temperature and then applied to the synthesis of surfactants bearing a different alkyl-chain length. Antibacterial activity evaluation, has been done performing several tests against Gram +\- and yeast strains; results confirmed that AATEABs bearing C11 (AUTEAB) and C12 (ADTEAB) alkyl chain possess highest activity which is remarkable high for ADTEAB. AATEABs may find applications as polymerizable coatings for watr-treatment membranes ( commercial or not) to be used in Pressure-Driven Membrane Processes or in any other membrane-based system in which antifouling properties may play an important role.  Chapter 4: Thin Film Composite Membrane fabrication for gas separation: Defect control and bench-scale demonstration Fourth chapter of this thesis work, concerns the preparation of TFC membranes to be used for CO2/N2 separation, on the relationship between TFC membrane material and membrane properties and the role of the protective layer in determining the amount of defects, which is a crucial aspect for all the gas separation-related processes. We report a simple and efficient procedure which can also be applied to for defect controlling during scale-up process and which is not valid for CO2 separation membranes only. Results demonstrate a correlation between the properties of protective layer and separation performances: in particular, the possibility to apply a coating film on commercial membrane permits the creation of membranes in which the amount of defect is dramatically reduced. Another crucial aspect discussed in chapter 4 concerns the thickness of protective layer used for defect control: in fact, whereas the presence of protective layer plays an important role defect-free membrane creation process, its thickness impacts on separation operation. With our method, the preparation of membranes with very thin protective layer ( 0.1 μm or below) is possible.
Ph CourseScienceand Engineering of Environmental, Structure and Energy. Ciclo XXXI
Keywords: Graphene; Transport properties; Membranes; Composite materials